PERBANDINGAN FASE PRODUKSI TELUR KALKUN TERHADAP FERTILITAS, SUSUT TETAS, DAYA TETAS, DAN BOBOT TETAS - Nike Anggrain; Tintin Kurtini; Dian Septinova (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2014)
Egg production phase consists of two phases which first production phases and second productionphase. The first of production phase in turkeys began at the 6.5 to 7,0 months of hen age, the peakproduction phase mains 9-10 ages, while the second of production phase on the life is more than14 months of the hen age. Egg production in the first phase of production is higher than of eggproduction in the second phase production.This is caused by the ability of the reproductive organs in the first production phase better than thesecond phase. The research was carried out on 1 March-12April 2013 held at the Ranch turkeyPekon Sukoharjo Natural Partners I, Sukoharjo District, District Pringsewu. Eggs were usedduring the study were turkey eggs as much as 60 egge with an average weight of 68,83 g egg onegg production phase of the 7 months of age and 82.45 g in egg production phase at 14 monthsage. This study used 2 treatment design, namely the egg production phase 7 months of hen age(T1) and egg production phase 14 months of hen age (T2), each treatment consisted of 10experimental units and each unit consists of experiments 3 eggs. Data were analyzed usingStudent's t-test with a significance level of 5%. Treatment of egg production of the first and secondphase of the turkey parent age 7 months and 14 months did not affect significant (P> 0.05) onfertility, hatchability turkey, and hatchability, whereas the hatching weight significantly (P <0.05)the turkey egg.